The sublimation of beauty (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
In this paper I try to show the change the concept of beauty has gone through when it has run parallel to the concept of the sublime in the modern world. I focus particularly on the loss of the revelatory potential attributed to the beauty by the Platonic thought and its heirs, and on the transfer of this capacity to the concept of the sublime from Kant onwards, although this capacity will be reduced to the immanent space. This change will have a radical influence on a series of basic concepts of art, among them, that of genius
Keywords: beautiful; sublime; Plato; Kant